Ecotourism and its prospects in a wildlife-non-hunting-area of central Thailand: Governance implications of tensions between national policies and local experiences - Dhakal, Subas (Institute of Archaeology, 2014)
Wildlife-Non-Hunting-Areas (WNHAs) in Thailand are categorized as managed resource sites equivalent to IUCN category VI protected areas. The majority of WNHAs in the country are proclaimed over wetlands that are locally, nationally, or globally significant. After acceding to the Convention on Wetlands of International Importance in 1998, called the Ramsar Convention, Thailand has progressively promoted ecotourism as a tool for the wise use of wetlands. While ecotourism has the potential to finance the management of natural resources and diversify livelihood options for the locals in or near WNHAs, the interplay between policies and people which largely shapes the success or failure of any ecotourism initiative remains under-explored. This paper responds to this gap and utilises the sustainable livelihoods framework to investigate the tensions between national policies and local experiences associated with promoting ecotourism within a WNHA in central Thailand. © Common Ground, Subas P. Dhakal, All Rights Reserved.